2009
DOI: 10.1007/s11027-009-9167-8
|View full text |Cite
|
Sign up to set email alerts
|

Fishery livelihoods and adaptation to climate change: a case study of Chilika lagoon, India

Abstract: Climate change, Adaptation, Livelihood, Sustainable livelihood approach, Chilika lagoon,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…The constraints that were reported are mainly associated with limited physical infrastructure and access to basic services like credit that characterize most fisher communities (Olago et al 2007;Iwasaki et al 2009;MRAG 2011). Therefore, providing these services can address the constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The constraints that were reported are mainly associated with limited physical infrastructure and access to basic services like credit that characterize most fisher communities (Olago et al 2007;Iwasaki et al 2009;MRAG 2011). Therefore, providing these services can address the constraints.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation prevails in the Chilika lagoon, India. Here, 97% of fishing communities depend solely on fishing for income generation [62]. In the fishing camps of Lake Kariba, the average number of livelihood activities in which each household is involved is higher in the wet season (1.7) than in the dry season (1.1).…”
Section: Community Characteristics and Livelihood Assetsmentioning
confidence: 99%
“…Case studies lend themselves to the complexities of climate change vulnerability research, allowing for the examination of multiple stressors that change over time and space (Ford et al, 2010b;Adger, 1999). Several authors have identified a need to conduct more in-depth, community studies that consider the complex, dynamic circumstances in which these adaptive strategies are employed (Iwasaki, 2009;Verner, 2010;Kronik & Verner, 2010). This study's use of a case study will thus allow for a more detailed, deeper understanding of the topic (Ford et al, 2010b).…”
Section: The Case Study Of Panaillomentioning
confidence: 99%